Categories of Intimate Partner Violence and Abuse Among Young Women and Men: Latent Class Analysis of Psychological, Physical, and Sexual Victimization and Perpetration in a UK Birth Cohort - Herbert, Annie (Journal of interpersonal violence, 2023)
BackgroundIn the UK, around one-third of young people are exposed to Intimate Partner Violence and Abuse (IPVA) by 21 years old. However, types of IPVA victimization in this population (psychological, physical, sexual), and their relationship with impact and perpetration are poorly understood.MethodsParticipants in a UK birth cohort reported IPVA victimization and perpetration by age 21. We carried out a latent class analysis, where we categorized IPVA by types/frequency of victimization, and then assigned individuals to their most probable class. Within these classes, we then estimated rates of reported: 1) types of negative impacts (sad, upset/unhappy, anxious, depressed, affected work/studies, angry/annoyed, drank/took drugs more); 2) types/frequency of perpetration.ResultsAmong 2130 women and 1149 men, 32% and 24% reported IPVA victimization (of which 89% and 73% reported negative impact); 21% and 16% perpetration. Victimization responses were well represented by five classes, including three apparent in both sexes: No-low victimization (characterized by low probabilities of all types of victimization; average probabilities of women and men belonging to this class were 82% and 70%); Mainly psychological (15% and 12%); Psychological and physical victimization (4% and 7%), and two classes that were specific to women: Psychological and sexual (7%); Multi-victimization (frequent victimization for all three types; 4%). In women, all types of negative impact were most common in the Psychological and sexual and Multi-victimization classes; for men, the Psychological and physical class. In women, all types of perpetration were most common for the Mainly psychological, Psychological and physical and Multi-victimization classes; in men, the Mainly psychological and Psychological and physical classes.DiscussionIn this study of young people, we found categories of co-occurrence of types and frequency of IPVA victimization associated with differential rates of negative impact and perpetrating IPVA. This is consistent with emerging evidence of IPVA differentiation and its variable impact in other populations.